Knowledge Management In Zakat Division Majlis Agama Islam Dan Adat Melayu Perak - Khafizatunnisa’ Jaapar; Mazlah Yaacob; Muhammad Yusri Yusof@ Salleh; Nurul Khairiah Khalid (Universiti Sains Islam Malaysia, 2024)
This paper is an attempt to address a practice of Knowledge Management(KM) in Zakat Division, Majlis Agama Islam Perak (MAIPk). Thus, there will be a discussion about KM aspects in knowledge capture, sharing and culture with special references to Zakat Division MAIPk. The purpose of the study is to discover conventional approach within zakat staff’s institution and at the same time provide the other suggestion especially in KM in order to improve their task by the fastest and the smartest way. Since this paper is a theoretical paper, thus it utilizes quantitative method as it employs empirical support within questionnaire and historical background. Hence, some basic finding is there are informal practicality of KM in Zakat Division. Based on interview, some Zakat Division are more preferred to use conventional KM method such as written mail, policies, filing and procedures rather than new method of KM such as email, facebook, e fililng and etc.